Evidence-based stragegies to inform urban design decision-making: the case of pedestrian movement behaviour. - Stanitsa, Avgousta (Cranfield University, 2022)
Walking is an essential mode of transportation, and pedestrian movement is a major influencing parameter in city design. Due to the complexity of pedestrian behaviour, new insights concerning the significance of factors affecting walking are challenging to obtain without the use of technology. Furthermore, despite the impact of decision-making in the design of buildings and places, there is currently a limited understanding concerning how urban design decisions are best made. This research aims to “assess the adoption of, and opportunities deriving from, data-driven innovation techniques in the design of urban spaces, by the analysis of pedestrian movement patterns in urban environments, and to evaluate how the integration of evidence-based strategies can be established in supporting decision-making in relation to future urban designs”. The research focuses on two groups of stakeholders: Decision-makers in designing buildings and places and End-users undertaking walking activities within urban space. In addressing the aim, a range of research methodologies has been developed and trialled. The work centres on an extended case study concerning a retail high-street locale in London, UK. This study makes several contributions to the immediate field of urban design research. Firstly, the findings advance the research methods applied to study pedestrian movement in urban environments. Secondly, the results offer real impact in practice by demonstrating the value and importance of adopting data-driven innovation techniques in decision-making processes in urban design via the adoption of a quantitative data- driven, evidence-based methodological framework. Thirdly, the findings support decision-making by presenting a novel methodological framework to assess pedestrian routing in urban environments utilising the classification of pedestrian behaviours and spatial visibility interactions. Finally, this study raises awareness of the critical challenges and opportunities, priorities, and potential development areas for applying evidence- based strategies in informing building and urban design decisions. The research presents a series of recommendations for enhancing data-driven innovation techniques in urban design decision-making processes.
Keywords: Urban planning; evidence-based decision-making; data-driven innovations; big data; pedestrian movement; design